An Analisis Pemahaman Membaca Dalam Teks Narasi Siswa Kelas XI SMA N1 Slogohimo - Michael Daniel Senewe; Lukman Al Hakim (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This study aims to analyze the students reading comprehension ability on narrative text based on the four levels of comprehension skills at eleventh Grade Students of SMA N1 Slogohimo. This research used qualitative descriptive research To describe the students reading comprehension in narrative text based on the four level comprehension skill for eleventh Grade Students of SMA N1 Slogohimo. To collect the data, the researcher used questionnaires and interview with the teacher and students. After collecting the data the researcher analyzed the data by using via data triangulation to analyzed qualitative data. To collect the data of questionnaire and interview, the researcher use questionnaire by Google Form. The data from questionnaire were analysed by using Likert scale. The result of this research showed that the students’ skill in understanding the implicit facts stated in an informational text, characters in a story, and any other information such as facts, vocabulary, times, and locations was quite high. It could be seen from the score distribution obtained by the students. The research showed that the students level of comprehension skills in comprehending narrative text is average. It can be concluded that the students had difficulties in creative comprehension skill, therefore the students should focus and pay attention on terms of identify reference without ignoring the other aspect of narrative text.Keyword: level of comprehension skill, reading, narrative text